An ephemerality paradox: Evidence of virtual semelparity in ephemeral pool‐breeding anurans. (10th October 2022) - Gould, John; Clulow, John; Herb, Frithjof; Clulow, Simon
Abstract: Oviparous species that reproduce in unpredictably variable environments risk depositing their eggs in situations that may become unsuitable for offspring survival at any time. This uncertainty often leads to selection for iteroparity as a form of bet‐hedging to spread offspring development spatially and temporally, thereby improving the odds of some cohorts experiencing optimal conditions. Paradoxically, an iteroparous mode appears to be the exception for a small number of amphibians that exploit temporary aquatic systems. In this study, we provide evidence of this paradox in an Australian anuran, the sandpaper frog, Lechriodus fletcheri, which breeds almost exclusively in small, highly ephemeral pools that often dry before the completion of tadpole development. A capture‐mark‐recapture study was conducted on a population over three consecutive breeding seasons, to determine how often adults returned to breeding sites within and between years and the extent of iteroparity. We found practically no adult returns between seasons, even though recapture events often occurred within season, suggesting that this species is virtually semelparous. A similar life history is apparent in other amphibians, suggesting that some species are able to persist in unpredictable environments by likely taking advantage of other forms of bet‐hedging in the absence of iteroparity. For L. fletcheri, we suggest that an extended breeding season may lend itself to the process of cohort splitting at a population level, resulting in the future reproductive activity of offspring from each generation being spread across multiple seasons. Our study shows how an iteroparous life history is not the only way to deal with environmental uncertainty. Abstract : Oviparous species that reproduce in unpredictably variable environments often select for an iteroparous life history to offset the high risk of reproductive failure per clutch. In this paper, we report that paradoxically, a small number of amphibians that exploit temporary aquatic systems for reproduction are short‐lived and virtually semelparous. This suggests that some species are able to persist in unpredictable environments by taking advantage of other forms of bet‐hedging in the absence of the reasonable a priori prediction of iteroparity.